Endoscopic Endonasal Approaches to the Medial Intraconal Space: Comparison of Transethmoidal and Prelacrimal Corridors - Li, Lifeng (Am J Rhinol Allergy, 2020)
BACKGROUND: Endoscopic transethmoidal and prelacrimal approaches can access the medial intraconal space (MIS). OBJECTIVE: This study aimed to compare advantages and drawbacks of these two approaches, and to explore their appropriate indications for management of lesions at various locations within the MIS. METHODS: Six injected cadaveric specimens were dissected using an endonasal approach performing a transethmoidal approach on one side and a prelacrimal approach on the contralateral side. The MIS was divided into three Zones: Zone 1 was defined as the area above the superior border of the medial rectus muscle (MRM), Zone 2 as the area between the MRM and the optic nerve, and Zone 3 as the area below the inferior border of MRM. The exposure provided by these two approaches to various Zones within the MIS was assessed and compared. RESULTS: The average height of Zone 1 to 3 was 10.35 ± 0.45 mm, 11.07 ± 0.59 mm, and 6.53 ± 0.59 mm, respectively. Both approaches provided adequate exposure of Zone 2 and 3; however, the prelacrimal approach provided direct exposure of the posterosuperior aspect of Zone 2 without retraction of MRM. Retraction of MRM was unavoidable using a transethmoidal approach to enhance further exposure. Access to Zone 1 was adequately achieved through the corridor between superior oblique muscle and MRM via a transethmoidal corridor. CONCLUSION: Conceptualizing the MIS into the three aforementioned Zones seems beneficial to select the optimal approach for lesions restricted to each specific Zone. Both the transethmoidal and prelacrimal approaches provide adequate exposure for select lesions in the MIS.